Tumor hypoxia evidences the differential regulation of Mdm2-p53 axis by PTEN in tumor derived vs. normal endothelial cells - Kinga Wilkus-Adamczyk; Klaudia Brodaczewska; Claudine Kieda (Scientific Reports)
Abstract Hypoxia, a condition of oxygen tension lower than physiological level, plays a crucial role in shaping the tumor microenvironment and modulates distinct cell populations activity. The tumor suppressor PTEN regulates angiogenesis, a process involving endothelial cells (ECs). Pathological in tumors, it is crucial for growth. As PTEN modulates p53, a key regulator of the ECs growth/angiogenic activity, it appears to be a target enabling the repair of the pathologic angiogenesis. This study aims to compare ECs derived from breast cancer (HBCa.MEC) site with those derived from the healthy breast tissue (HBH.MEC). Hypoxia increased angiogenic activity in HBCa.MEC vs. HBH.MEC, as showed an increased. Ability to form vessels in vitro. Low pO2 reduced the total level of Mdm2 and PTEN protein expression leading to elevated levels of their phosphorylation-dependent activity in HBCa.MEC, what was not changed in healthy ECs. Additionally, when Mdm2-p53 interaction was inhibited, hypoxic HBCa.MEC angiogenic activity was reduced reaching the normoxic ECs response. In conclusion, the PTEN-mediated control of pathological angiogenesis occurs by modulation of Mdm2/p53 interaction in the context of breast tumor microenvironment. PTEN emerges as a potential therapeutic target for normalizing tumor vessels in breast cancer treatment strategies.